ENDOSCOPIC FENSETRATION OF THIRD VENTRICULAR CYST - Khalid N Mayah (Basrah Journal of Surgery, 2006)
Abstract Arachnoids cyst is a common pathology although it is rarely to be in the third ventricle. A twelve years child has a third ventricle arachnoids cyst that leads to hydrocephalus, the cyst has been fenestrated by endoscope, most of the symptoms that sustained over five years has been relieved.